2023
DOI: 10.1021/jacsau.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Interfacial Electronic Pd–Si Interaction Boosts Catalysis via Accelerating O2 and H2O Activation

Abstract: Engineering the interfacial structure between noble metals and oxides, particularly on the surface of non-reducible oxides, is a challenging yet promising approach to enhancing the performance of heterogeneous catalysts. The interface site can alter the electronic and d-band structure of the metal sites, facilitating the transition of energy levels between the reacting molecules and promoting the reaction to proceed in a favorable direction. Herein, we created an active Pd–Si interface with tunable electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…The peaks at low temperature (400–500 °C) were ascribed to active OH groups, which were related to the Pd species, and attributed to the interfacial OH groups of the Pd and SiO 2 carrier. 37 The peaks at 600–900 °C were assigned to intrinsic Si–OH of SiO 2 (confirmed by experimental data shown in Fig. S8†).…”
Section: Resultssupporting
confidence: 60%
“…The peaks at low temperature (400–500 °C) were ascribed to active OH groups, which were related to the Pd species, and attributed to the interfacial OH groups of the Pd and SiO 2 carrier. 37 The peaks at 600–900 °C were assigned to intrinsic Si–OH of SiO 2 (confirmed by experimental data shown in Fig. S8†).…”
Section: Resultssupporting
confidence: 60%
“…Generally, SiO 2 is identified as an inert component of the catalysts to disperse and support metal nanocrystals. Studies indicated that the newly constructed metal–Si interface, accompanied by charge transfer, displayed superior catalytic performance in diverse important reactions, such as hydrogenation/dehydrogenation, , O 2 activation, electrocatalytic reactions, , and CO 2 conversion. ,, …”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, MOFs have attracted much attention in various fields such as gases, supercapacitors, dye adsorption and drug delivery due to their unique structural and chemical properties. 23 Especially in catalysis, MOFs, as emerging porous nonhomogeneous catalysts, show remarkable potential 24 in reactions such as oxidations, 25 reductions, 26 couplings 27 and cyclisations. 28 [Cu 3 (BTC) 2 (H 2 O) 3 ] n (Cu-BTC, HKUST-1), as a typical representative of MOFs, has been widely used in a variety of organic reactions, 29 including couplings, 30 cyclizations, 31 oxidizations 32 and boronation reactions.…”
Section: Introductionmentioning
confidence: 99%